Arsenic exposure is associated with diminished insulin sensitivity in non‐diabetic Amish adults. Issue 6 (14th January 2016) - Park, Sung Kyun; Peng, Qing; Bielak, Lawrence F.; Silver, Kristi D.; Peyser, Patricia A.; Mitchell, Braxton D.
Abstract: Background: Substantial evidence supports an association between diabetes and arsenic at high exposure levels, but results are mixed at low exposure levels. The aetiology of diabetes involves insulin resistance and β‐cell dysfunction. However, only a few epidemiologic studies have examined measures of insulin resistance and β‐cell function in relation to arsenic exposure, and no studies have tested for associations with the oral glucose tolerance test (OGTT). We examined the association between urinary total arsenic and OGTT‐based markers of insulin sensitivity and β‐cell function. Methods: We studied 221 non‐diabetic adults (mean age = 52.5 years) from the Amish Family Diabetes Study. We computed OGTT‐based validated measures of insulin sensitivity and β‐cell function. Generalized estimating equations accounting for sibship were used to estimate associations. Results: After adjusting for age, sex, waist‐to‐hip ratio and urinary creatinine, an interquartile range increase in urinary total arsenic (6.24 µg/L) was significantly, inversely associated with two insulin sensitivity measures (Stumvoll metabolic clearance rate = −0.23 mg/(kg min), (95% CI: −0.38, −0.089), p = 0.0015; Stumvoll insulin sensitivity index = −0.0029 µmol/(kg min pM), (95% CI: −0.0047, −0.0011), p = 0.0015). Urinary total arsenic was also significantly associated with higher fasting glucose levels (0.57 mg/dL (95% CI: 0.06, 1.09) per interquartile range increase, p = 0.029). No significant associations were found between urinary total arsenic and β‐cell function measures. Conclusions: This preliminary study found that urinary total arsenic was associated with insulin sensitivity but not β‐cell function measures, suggesting that low‐level arsenic exposure may influence diabetes risk through impairing insulin sensitivity. Copyright © 2015 John Wiley & Sons, Ltd.